NDRG1 functions in LDL receptor trafficking by regulating endosomal recycling and degradation - Pietiäinen, Vilja; Vassilev, Boris; Blom, Tomas; Wang, Wei; Nelson, Jessica; Bittman, Robert; Bäck, Nils; Zelcer, Noam; Ikonen, Elina (Journal of cell science, 2013)
N-myc downstream-regulated gene 1 (NDRG1) mutations cause Charcot-Marie-Tooth disease type 4D (CMT4D). However, the cellular function of NDRG1 and how it causes CMT4D are poorly understood. We report that NDRG1 silencing in epithelial cells results in decreased uptake of low-density lipoprotein (LDL) due to reduced LDL receptor (LDLR) abundance at the plasma membrane. This is accompanied by the accumulation of LDLR in enlarged EEA1-positive endosomes that contain numerous intraluminal vesicles and sequester ceramide. Concomitantly, LDLR ubiquitylation is increased but its degradation is reduced and ESCRT (endosomal sorting complex required for transport) proteins are downregulated. Co-depletion of IDOL (inducible degrader of the LDLR), which ubiquitylates the LDLR and promotes its degradation, rescues plasma membrane LDLR levels and LDL uptake. In murine oligodendrocytes, Ndrg1 silencing not only results in reduced LDL uptake but also in downregulation of the oligodendrocyte differentiation factor Olig2. Both phenotypes are rescued by co-silencing of Idol, suggesting that ligand uptake through LDLR family members controls oligodendrocyte differentiation. These findings identify NDRG1 as a novel regulator of multivesicular body formation and endosomal LDLR trafficking. The deficiency of functional NDRG1 in CMT4D might impair lipid processing and differentiation of myelinating cells.